Editorial - Dixit, Sudhir; Jefferies, Nigel; Debbah, Merouane; Skouby, Knud Erik; Alexiou, Angeliki (Journal of Mobile Multimedia, 2022)
Welcome to this special issue containing some of the best papers pre- sented at the Wireless World Research Forum (WWRF) meetings at Kuala Lumpur, Malaysia, in January 2021 and Paris, France, in December 2021. The Malaysia meeting had the theme Hyperconnectivity (Beyond 5G, Oppor- tunities & Challenges) and the Paris meeting had the theme From Connected Things to Connected Intelligence. Both themes are well aligned with current technology trends and attracted a large number of high quality presentations and papers to the various plenary sessions and working groups. Hyperconnectivity offers us the chance to reach for the goal of ubiquitous connectivity when everyone and everything can be part of an intelligently managed and limitless, yet sustainable, secure and reliable, Smart Connec- tivity System. At the same time, the widespread introduction of Artificial Intelligence (AI) and Machine Learning (ML) technology will provide a strong impetus towards improved network performance and cost-efficiency for current and even more for next generation mobile systems. Beyond 5G, services and networks will be managed more autonomously and are expected to offer increased flexibility and adaptability everywhere. Networks and applications will need to become more intelligent, self-learning and context dependent. AI’s potential impact on consumer, society and industry- relevant aspects for end-to-end communication systems and use cases will be tremendous. Future Cognitive Communication Systems are envisioned to be continuously learning, self-optimizing and capable of transitioning from just connecting humans and things to connecting, sensing and actuating anything, intelligently and in a purpose driven manner.